Verba Majemuk Nukeru dalam Bahasa Jepang - Elizabeth Ika Hesti Aprilia Nindia Rini; Daniel Andre Sinaga (Universitas Diponegoro, 2022)
This paper discusses “Compound Verb Nukeru in Japanese Sentences”. The objective of this research is to describe the structure and the meaning of Japanese compound verb nukeru. The data taken from electronic mass media, electronic articles and, Japanese language websites. Listening method with the tapping technique as the basic technique and the free-of-conversation listening technique (SBLC) and the note-taking technique as the continuation technique are used in providing the required data. Furthermore, analysis of the structure and meaning of the compound verb nukeru are carried out using the agih method with the direct element division (BUL) technique and the top down technique. The presentation of the results of data analysis are carried out using an informal method.. Based on the data analysis, it is concluded that the compound verb nukeru is formed from various pre-verbs (V1) and back-verb; nukeru (V2). Furthermore, the compound verb nukeru can be attached to intransitive and transitive, progressive, and stative, volitional and non volitional and motion verbs. The compound verb nukeru has 8 meanings, they are penetration, breakthrough/breakout in a fight/game/match, breakthrough/penetration of space, the process of passing from a space, crossing; shortcut; pass; through, excellence; quality; prominence; superiority, renunciation; dismantlement; withdrawal; secession; leave, and sold out in high prices. Meanwhile, the meaning relationship between the pre-verb (V1) and the back-verb (V2); nukeru consists of hobun kankei or complementary relationships, shuushoku-hishuushoku kankei (prefix affixation of verbs), shujutsu-hosoku kankei, and jukugou fukugoudoushi. <a href=